The Effectiveness Of The Virtual Interactive Media InaRISK Personal On Flood Disaster Preparedness Among Adolescents - Rachmawan, Ivan; Hidayat, Wahyu Santoso; Prasetyawan, Riyan Dwi; Iswahyudi, Ulul Azmi (Nursing Information Journal, 2025)
Floods are among the most frequent natural disasters in Indonesia and have a substantial negative impact on communities, particularly vulnerable groups such as children and adolescents. The consequences of flooding include not only material losses but also disruptions to social, educational, and health activities. Adolescents, as part of a critical developmental stage, require appropriate disaster education to increase their awareness and preparedness in facing such events. This study aims to examine the effectiveness of InaRISK Personal, an interactive virtual media developed by the Indonesian government, in improving flood disaster preparedness among adolescents. This research employed a pre-experimental design with a one-group pretest-posttest approach. The study was conducted at SMP Negeri 1 Kalipuro, Banyuwangi, a flood-prone area in East Java. The sample consisted of 85 students, selected through simple random sampling. Data were collected using a 30-item disaster preparedness questionnaire, which had previously undergone validity and reliability testing. The data were analyzed using the Wilcoxon signed-rank test. The results revealed a significant difference between pretest and posttest scores, with a p-value of 0.000 (p < 0.05), indicating that the use of InaRISK Personal significantly improved students’ disaster preparedness levels. The study also observed a shift in preparedness categories, with most students moving from "almost prepared" to "prepared" or "very prepared" after the intervention. this study highlights the practical potential of InaRISK Personal as a digital tool to support school-based disaster education. While digital platforms in disaster preparedness are not entirely new, the application of InaRISK Personal among adolescents in formal education settings—particularly in disaster-prone regions—adds context-specific insights that support its wider adoption.